2022
DOI: 10.3389/fpls.2022.1038684
|View full text |Cite
|
Sign up to set email alerts
|

Wild Helianthus species: A reservoir of resistance genes for sustainable pyramidal resistance to broomrape in sunflower

Abstract: Orobanche cumana Wall., sunflower broomrape, is one of the major pests for the sunflower crop. Breeding for resistant varieties in sunflower has been the most efficient method to control this parasitic weed. However, more virulent broomrape populations continuously emerge by overcoming genetic resistance. It is thus essential to identify new broomrape resistances acting at various stages of the interaction and combine them to improve resistance durability. In this study, 71 wild sunflowers and wild relatives a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…However, as mentioned above, this was not very common and remained cell autonomous. In addition, no evidence of cell death was observed at the later stages (Chabaud et al, 2022). Altogether, these results showed that the parasitic intrusive cells penetrate the host root cells intracellularly, as a result of degradation of the host cell wall and formation of a new host trans-cellular apoplastic compartment for haustorium accommodation.…”
Section: Intrusive Cells Penetrate a New Apoplastic Compartmentmentioning
confidence: 67%
See 1 more Smart Citation
“…However, as mentioned above, this was not very common and remained cell autonomous. In addition, no evidence of cell death was observed at the later stages (Chabaud et al, 2022). Altogether, these results showed that the parasitic intrusive cells penetrate the host root cells intracellularly, as a result of degradation of the host cell wall and formation of a new host trans-cellular apoplastic compartment for haustorium accommodation.…”
Section: Intrusive Cells Penetrate a New Apoplastic Compartmentmentioning
confidence: 67%
“…The number of dividing root cell layers and the length of the dividing zone were highly variable (for example, from 1 cortical cell to > 30 cells in a row). These divisions may account for root hypertrophy that was previously observed at the site of 14-dai attachments in rhizotrons (Chabaud et al, 2022). These divisions could be induced indirectly (host hormonal regulation) or directly by the parasitic plant (hormonal release: such as auxin (Ishida et al, 2016) or cytokinin (Spallek et al, 2017)).…”
Section: Divisions Are Induced At Very Early Stagesmentioning
confidence: 75%
“…The virulence identified in the Greek populations in part explicate why they could infest the race A-E resistant sunflower hybrids planted at Drama and Orestiada. The appearance of increasingly virulent populations in recent years could be explained by the intensity of sunflower breeding for resistance to new strains of broomrape, thereby exerting immense selection pressure on the parasite to evolve more virulent races ( Molinero-Ruiz et al., 2015 ; Miraille et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent progress in sunflower genomics provides additional tools for plant breeders to find durable solutions against broomrape spread and virulence in sunflower ( Cvejić et al., 2020 ). The discovery and breeding of multiple resistant genes via a pyramiding approach will drastically decrease the risk of evolution of virulent broomrape races ( Velasco et al., 2016 ; Miraille et al., 2022 ). For the long-term management of the holoparasite, it is imperative to adopt an integrated approach combining chemical and genetic control with sound agronomic practices, including rotation with trap crops, use of clean seeds and measures to limit seed spread via agricultural machinery and tillage tools ( Rubiales et al., 2009 ; Habimana et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…As an obligate holoparasite, O. cumana has fully lost the ability to photosynthesize. Herbicide strategies such as imidacloprid in combination with herbicide-resistant sunflower [9,10], crop rotation including non-host bait crops that induce O. cumana seed germination [11] and resistant varieties are commonly used for parasitic weed management [12]. However, these methods have some limitations and can easily increase the financial burden on farmers.…”
Section: Introductionmentioning
confidence: 99%